2010
DOI: 10.1105/tpc.110.076133
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis

Abstract: Heterosis refers to the phenomenon that progeny of diverse varieties of a species or crosses between species exhibit greater biomass, speed of development, and fertility than both parents. Various models have been posited to explain heterosis, including dominance, overdominance, and pseudo-overdominance. In this Perspective, we consider that it might be useful to the field to abandon these terms that by their nature constrain data interpretation and instead attempt a progression to a quantitative genetic frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
388
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(416 citation statements)
references
References 69 publications
7
388
0
4
Order By: Relevance
“…Reduction in CCA1 expression amplitudes or transcript levels promotes the expression of downstream genes that are negatively regulated by CCA1 abundance, as shown in Arabidopsis diploids and allopolyploids (Ni et al, 2009). This altered circadian regulation could affect photosynthetic and metabolic pathways that are altered in F1 hybrids (Fujimoto et al, 2012;Meyer et al, 2012) as well as overall regulatory networks related to growth and development (Birchler et al, 2010).…”
Section: A Model For Parent-of-origin Effects On Altered Circadian Rhmentioning
confidence: 99%
“…Reduction in CCA1 expression amplitudes or transcript levels promotes the expression of downstream genes that are negatively regulated by CCA1 abundance, as shown in Arabidopsis diploids and allopolyploids (Ni et al, 2009). This altered circadian regulation could affect photosynthetic and metabolic pathways that are altered in F1 hybrids (Fujimoto et al, 2012;Meyer et al, 2012) as well as overall regulatory networks related to growth and development (Birchler et al, 2010).…”
Section: A Model For Parent-of-origin Effects On Altered Circadian Rhmentioning
confidence: 99%
“…6). Heterozygous loci may be preferentially maintained during the early rounds of breeder selection, as individuals with higher rates of heterozygosity may exhibit greater yields or other advantageous traits due to heterosis (Birchler et al, 2010). Genetic theory predicts, on average, a halving of heterozygous loci with every self-pollination following a given cross.…”
Section: Selection and Intracultivar Heterogeneitymentioning
confidence: 99%
“…Under the F ∞ (or F 2 ) metric model, the heritabilities for the ten main QTL varied from 0.00 to 12.69% (0.00 to 13.55%) in the L 1 population and from 0.00 to 5.44% (0.00 to 6.07%) in the L 2 population; those for the three epistatic QTL were 0.51, 7.31, and 0.00% (0.14, 4.10 and 0.00%) in the L 1 population, and 15.70, 7.83, and 4.98% (23.77, 2.18 and 9.47%) in the L 2 population; the total heritabilities explained by all the main and epistatic QTL were 51.28 and 42.02% (47.95 and 35.26%) in the above two populations, respectively (Table S4). Judged by pure main effects, QTL 3 and QTL 10 were additive; QTL 1 and QTL 4 were partially dominant; QTL 2 was completely dominant; QTL 6 , QTL 7 and QTL 9 were overdominant; and QTL 5 and QTL 8 had no pure main effects (Tables 3, 5, S5 and S7). While judged by augmented main effects under the F ∞ metric model, QTL 5 and QTL 8 turned to complete dominance; the other eight QTL had the same types as the original ones, although degrees of dominance for some QTL (QTL 4 and QTL 7 ) changed (Tables 3 and 5).…”
Section: Monte Carlo Simulation Studiesmentioning
confidence: 99%
“…The results showed that the RIL-based NCIII design was superior to the F 2 -based NCIII design for mapping heterotic QTL. Although the augmented main effects ( * a and * d ) were all unbiasedly estimated with satisfactory powers and the augmented epistatic effects (  i and  i ) between QTL 4 and QTL 7 , which consisted of two epistatic effects with the same sign, were also well mapped. The augmented epistatic effects ( i between QTL 5 and QTL 8 ), which consisted of two epistatic effects of equal strength in opposite directions, were very poorly mapped, even though both sample size and replication number were at high levels (n=500 and m=10), i.e., the powers in the detection of  58 i and  58 i in the F 2 -based NCIII design were 0.50 and 2.00% under the F ∞ metric model, and 0.50 and 18.5% under the F 2 metric model [41].…”
Section: Monte Carlo Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation